2020
DOI: 10.1186/s13601-020-00321-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation of health and care to sustain Planetary Health: The MASK proof-of-concept for airway diseases—POLLAR symposium under the auspices of Finland’s Presidency of the EU, 2019 and MACVIA-France, Global Alliance against Chronic Respiratory Diseases (GARD, WH0) demonstration project, Reference Site Collaborative Network of the European Innovation Partnership on Active and Healthy Ageing

Abstract: In December 2019, a conference entitled "Europe That Protects: Safeguarding Our Planet, Safeguarding Our Health" was held in Helsinki. It was co-organized by the Finnish Institute for Health and Welfare, the Finnish Environment Institute and the European Commission, under the auspices of Finland's Presidency of the EU. As a side event, a symposium organized as the final POLLAR (Impact of air POLLution on Asthma and Rhinitis) meeting explored the digital transformation of health and care to sustain planetary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
0
21
0
2
Order By: Relevance
“…MASK‐air ® (Mobile Airways Sentinel NetworK) is an example of such an approach. This app has a monitoring questionnaire which assesses the daily impact of allergic symptoms (as well as medication use) on the user 5–7 . A recent MASK‐air ® study has assessed a modified CSMS approach following the approval of new medications (mCSMS) 3,8 …”
Section: Introductionmentioning
confidence: 99%
“…MASK‐air ® (Mobile Airways Sentinel NetworK) is an example of such an approach. This app has a monitoring questionnaire which assesses the daily impact of allergic symptoms (as well as medication use) on the user 5–7 . A recent MASK‐air ® study has assessed a modified CSMS approach following the approval of new medications (mCSMS) 3,8 …”
Section: Introductionmentioning
confidence: 99%
“… App zur Messung von Umweltdaten und Tagebuchfunktionen zu Allergien 34 Videokonferenzen mit Versorger*innen samt Aufzeichnungen von Parametern nach Krankenhausentlassung 53 App in Verbindung mit Inhalator zur Förderung der Medikamentenadhärenz 18 …”
Section: Ergebnisseunclassified
“…Using the MASK‐air (Mobile Airways Sentinel Network) approach, 135,136 it was recently found that AIT was improving allergic symptoms and work productivity 137 …”
Section: Ait In Real‐life Carementioning
confidence: 99%